2021
DOI: 10.1161/jaha.121.021818
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Black Race, Clinical Severity, and Management of Acute Pulmonary Embolism: A Retrospective Cohort Study

Abstract: Background Existing evidence indicates Black patients have higher incidence of pulmonary embolism (PE) and PE‐related mortality compared with other races/ethnicities, yet disparities in presenting severity and treatment remain incompletely understood. Methods and Results We retrospectively queried a multihospital healthcare system for all hospitalizations for acute PE (2012–2019). Of 10 329 hospitalizations, 8743 met inclusion criteria. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
3
32
3
Order By: Relevance
“…However, other characteristics observed to be associated with IVCF placement and retrieval variability do not have clinical justification. The observed variations by geographic region and race, although consistent with what other studies have shown [17,19,20,27,28], suggest possible differences in regional clinical practice patterns and access to care. Phillips et al [28] recently observed among a cohort of patients with acute PE that Black patients presented with higher PE severity than White patients, even after matching on age and sex and adjusting for both clinical and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, other characteristics observed to be associated with IVCF placement and retrieval variability do not have clinical justification. The observed variations by geographic region and race, although consistent with what other studies have shown [17,19,20,27,28], suggest possible differences in regional clinical practice patterns and access to care. Phillips et al [28] recently observed among a cohort of patients with acute PE that Black patients presented with higher PE severity than White patients, even after matching on age and sex and adjusting for both clinical and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 87%
“…The observed variations by geographic region and race, although consistent with what other studies have shown [17,19,20,27,28], suggest possible differences in regional clinical practice patterns and access to care. Phillips et al [28] recently observed among a cohort of patients with acute PE that Black patients presented with higher PE severity than White patients, even after matching on age and sex and adjusting for both clinical and socioeconomic factors. In that same study, Black patients were also less likely to receive an intervention of any kind, even after stratifying by PE severity.…”
Section: Discussionsupporting
confidence: 87%
“…1,4,8,9,51 Several studies have described differences in the frequency of adverse outcomes in Black and White patients with VTE. 52 One study reported that Black individuals with PE were more likely to present with a more clinically severe event, 53 and a second study noted that Black individuals were more likely to be hospitalized than White individuals with PE. 54 Although we did not collect information about hospitalization following a new diagnosis of PE, we did not observe a difference in the use of thrombolytic therapy or embolectomy in Black compared to White patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a recent publication from a multicenter retrospective review, Phillips found that African American patients are more likely to present with higher severity of PE compared to Caucasians; African Americans were less likely to receive an intervention, but this had no impact on in-hospital mortality. 13…”
Section: Discussionmentioning
confidence: 99%